Severe Aortic Valve Stenosis: Symptoms, Biochemical Markers, and Global Longitudinal Strain - Bottaro, Giuseppe (J Cardiovasc Echogr, 2020)
BACKGROUND: According to the actual guidelines regarding severe aortic valve stenosis (AS), symptoms are the most important trigger for aortic valve replacement (AVR). However, the objective analysis of cardiological clinic can be confused, considering the aging population this disease affects and the comorbidities. OBJECTIVES: Looking for an objective marker of disease, useful for scheduling the correct AVR, we researched the relation between some biochemical markers of left ventricular (LV) dysfunction and its global longitudinal strain. MATERIALS AND METHODS: We analyzed 74 consecutive patients (82 ± 4 years) with severe AS. We identified 61 patients with symptoms (angina, dyspnea, and syncope) and 13 asymptomatic patients. The clinical and echocardiographic parameters were compared between these two groups. LV ejection fraction (LVEF), LV global longitudinal strain (LVGLS), NT-pro-B-type brain natriuretic peptide (BNP), troponin T (TNT), creatine kinase-MB (CPK-MB), and myoglobin were determined at the time of evaluation. RESULTS: Compared with the asymptomatic group, patients in the symptomatic group had a lower LVGLS (P = 0.002) and an increased pro-BNP (P = 0.0002). LVGLS showed a good correlation with pro-BNP as a marker of myocardial damage, with a linear increase of pro-BNP in patients with a linear decrease of LVGLS (r = 0.43). Despite the normal value of LVEF > 50% in asymptomatic patients, some of them (46%) have an early dysfunction of LVGLS. No other statistically significant difference emerged from the biochemical analysis, in TNT (P = 0.29), CPK-MB (P = 0.36), and myoglobin (P = 0.38). CONCLUSIONS: Pro-BNP and LVGLS can be considered an objective marker of clinical severity of AS disease, useful for management and scheduling of AVR, especially in asymptomatic patients.